2021
DOI: 10.1016/j.ejphar.2021.174196
|View full text |Cite
|
Sign up to set email alerts
|

Role of leukotriene pathway and montelukast in pulmonary and extrapulmonary manifestations of Covid-19: The enigmatic entity

Abstract: Severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2), the responsible agent for the coronavirus disease 2019 (Covid-19), has its entry point through interaction with angiotensin converting enzyme 2 (ACE2) receptors, highly expressed in lung type II alveolar cells and other tissues, like heart, pancreas, brain, and vascular endothelium. This review aimed to elucidate the potential role of leukotrienes (LTs) in the pathogenesis and clinical presentation of SARS-CoV-2 infection, and to reveal the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 68 publications
0
48
0
2
Order By: Relevance
“…It was suggested that montelukast can directly impact on COVID-19 [92], by having an anti-viral effect, or by suppression of heightened cytokine release in response to the virus [93][94][95][96]. Montelukast can block Cysteinyl-leukotriene in different organs or indirectly through inhibition of the NF-κB signaling pathway [97].…”
mentioning
confidence: 99%
“…It was suggested that montelukast can directly impact on COVID-19 [92], by having an anti-viral effect, or by suppression of heightened cytokine release in response to the virus [93][94][95][96]. Montelukast can block Cysteinyl-leukotriene in different organs or indirectly through inhibition of the NF-κB signaling pathway [97].…”
mentioning
confidence: 99%
“…One of possible explanations of differential susceptibility among carriers of different GSTP1 alleles may be the variations in regulatory roles of GSTP1. It is noteworthy to mention that, apart from its well-established role in detoxification and antioxidant protection, GSTP1 also exhibits leukotriene synthase activity, thus influencing pulmonary and extrapulmonary manifestations of COVID-19 ( Al-Kuraishy et al, 2021 ). Still, the data on the effect of different GSTP1 genetic variants on LTC4 synthesis are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological approach may also be applied to treat acute uncomplicated cases. However, more treatment options are required, thus necessitating the search for newer therapeutic agents ( 20 , 21 ). Presently, the WHO and other stakeholders are faced with the task to discover effective therapeutic agents to combat SARS-CoV-2 or make possible the fast development of vaccine(s) that prevent the disease.…”
Section: Covid-19 Transmissionmentioning
confidence: 99%